1981
DOI: 10.1002/bjs.1800680904
|View full text |Cite
|
Sign up to set email alerts
|

Vertical forces acting on the feet of diabetic patients with neuropathic ulceration

Abstract: The vertical forces acting on the sole of the foot in walking have been measured in 24 diabetic patients with neuropathic ulceration of the foot using a load-sensitive surface divided into 128 load cells, and compared with those in two groups of controls: (a), 21 diabetic patients with peripheral neuropathy but no ulceration and (b) 47 normal individuals. The results showed that the patients with neuropathic ulceration were significantly heavier, that diabetic patients with neuropathy, with or without ulcerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0
3

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(60 citation statements)
references
References 5 publications
5
52
0
3
Order By: Relevance
“…This phenomenon was previously reported in relation to determinants of DFU [7,8,21,26]. The hallux has been determined as a chief pressure point in patients within a high risk category of ulceration [21,22]. However, this study recorded similar pressures at the hallux in both groups; this was a novel finding.…”
Section: Dm Patients (N=19)supporting
confidence: 73%
See 1 more Smart Citation
“…This phenomenon was previously reported in relation to determinants of DFU [7,8,21,26]. The hallux has been determined as a chief pressure point in patients within a high risk category of ulceration [21,22]. However, this study recorded similar pressures at the hallux in both groups; this was a novel finding.…”
Section: Dm Patients (N=19)supporting
confidence: 73%
“…Many studies concluded that the presence of neuropathy was responsible for a major increase in plantar pressure across all findings [8,19,20]. Armstrong et al [21] and Ctercteko et al [22] along with others [23][24][25] have concluded that the hallux, heel and mid-metatarsal regions are those most inclined to develop calluses and ulceration. Van Schie et al [26] investigated the effect of arch index and body mass on plantar pressure for DM subjects and did not detect any difference in peak plantar pressure between the healthy and pathological groups.…”
Section: Introductionmentioning
confidence: 99%
“…
Diabetic foot ulcers are frequently severe at the plantar aspect of the first metatarsal head, and mechanical forces on the sole of the foot while standing and walking contribute to the development and progression of the wound [1,2]. Sensory neuropathy associated with loss of protective sensation allows abnormal mechanical forces to cause painless injury including skin wound and asymptomatic bone fracture [3].
…”
mentioning
confidence: 99%
“…The 36 diabetic patients consisted of 12 patients with superficial foot ulcers and 24 patients free from this disease. We measured fat to water and phosphocreatine to inorganic phosphate (PCr:Pi) ratios and calculated the intracellular pH of resting plantar muscles by depth-resolved surface-coil spectroscopy using an 1 H- 31 P double tuned coil. Furthermore, foot vasculature, fat and PCr contents of plantar muscles were visualised by phase-contrast angiography, T 1 -weighted spin-echo imaging and 31 P-chemical shift imaging.…”
mentioning
confidence: 99%
“…Diabetes-associated neuropathy, peripheral vascular disease, and infection all contribute to the process that produces ulceration and diabetic foot disease 12,[14][15][16][17][18][19][20] . Altered mechanical forces, especially high plantar pressures, are also an important factor [15][16][17][21][22][23][24][25] . Although a specific ulcer-producing pressure threshold has not been identified and appears to vary according to patient-related characteristics, reduction of high plantar pressure in feet that have lost protective sensation is the cornerstone of current prevention and treatment 15,17,19,20,22,26,27 .…”
mentioning
confidence: 99%